An Analysis of Production and Sales of Choerospondias Axillaris - Noora, Shrestha (International journal of Horticulture, Agriculture and Food science, 2020)
Choerospondias Axillaris, locally known as Lapsi in Nepal, is a high potential fruit cultivated for revenue generation mainly in eastern and central region of Nepal. This paper discusses the analysis of price, and sales of Lapsi in Kalimati Fruit and Vegetable Market in Kathmandu. In this market, the arrival of Lapsi had been endlessly decreasing from 520330 Kg in 2000/2001 to 17300 Kg in 2017/18 and the percentage increase in the average price was found to be 117.43. Out of all the fruit and vegetables, the average percentage coverage of Lapsi fruit was 0.076. There is significant negative correlation (r = -0.53) between average price (Rs. per Kg) and quantity in kg of Lapsi. The annual sales value for the year 2019/2020 is estimated to be Rs. 17091.17.